Parametric Modeling and Motion Simulation of Chain Drive based on the Creo 2.0 - Zhao Tao; Jiang Guoping (Jixie chuandong)
Chain drive relying on the sprocket teeth meshing with the chain link to transmit motion and power,it is one of the most important transmission mode in the modern machinery manufacturing industry,and the application of roller chain is most.As the chain drive is a disturbing movement,its assembly relationships and movement characteristic are complex.By using Creo 2.0software and taking single row roller chain as example,the a single chain link modeling,assembly are carried out.Through the guide curve,all the chain links are imported for assembly,and its motion simulation is carried out,a reference for the design of modern mechanical chain drive parametric modeling and motion simulation is provided.